2018
DOI: 10.3758/s13421-018-0881-x
|View full text |Cite
|
Sign up to set email alerts
|

Learning how to exploit sources of information

Abstract: How is our strategy for forming memories shaped by experience with a task? Previous work using surprise questions (i.e., unexpected by the participant) has shown a remarkable inability to report attributes of an attended target in a search display. This representational poverty presumably reflects a form of information exploitation, in which control processes specialize the conversion of available information into memory representations. We hypothesize that such control is refined by repeated experience with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
(34 reference statements)
2
32
1
Order By: Relevance
“…Specifically, it would suggest that dimensional selection, when it occurs, does select out of consciousness (as it is, presumably, possible only when the to-be-selected dimension can be phenomenally differentiated-i.e., consciously perceived as separate-from the irrelevant ones). This state of affairs is different from the previously demonstrated irrelevance-induced blindness (Eitam et al, 2013;Eitam et al, 2015) or the related phenomenon of attribute amnesia (Chen & Wyble, 2015;Wyble et al, 2018). The latter is argued to stem from rapid forgetting, and the former is thought to be based on so-called Posnerian selection (feature, object, or space based), and for which dimensional separability is irrelevant.…”
Section: Different Types Of Cognitive Bblindness^?contrasting
confidence: 59%
See 4 more Smart Citations
“…Specifically, it would suggest that dimensional selection, when it occurs, does select out of consciousness (as it is, presumably, possible only when the to-be-selected dimension can be phenomenally differentiated-i.e., consciously perceived as separate-from the irrelevant ones). This state of affairs is different from the previously demonstrated irrelevance-induced blindness (Eitam et al, 2013;Eitam et al, 2015) or the related phenomenon of attribute amnesia (Chen & Wyble, 2015;Wyble et al, 2018). The latter is argued to stem from rapid forgetting, and the former is thought to be based on so-called Posnerian selection (feature, object, or space based), and for which dimensional separability is irrelevant.…”
Section: Different Types Of Cognitive Bblindness^?contrasting
confidence: 59%
“…Importantly, various pieces of evidence suggest that a forgetting-based explanation is not adequate for irrelevancebased blindness (Eitam et al, 2015;Eitam et al, 2013). First, if forgetting was a key factor, one would expect to find an order effect such that reporting the irrelevant stimulus would be worse when probed second (after reporting the relevant stimulus) compared with when it is probed first; yet no such effect was found (Eitam et al, 2013;Wyble et al, 2018; see Experiment 2 of the current study). Second, a recent study (Wyble et al, 2018) found that with the attribute amnesia paradigm, increasing the number of relevant-probed trials before asking about the irrelevant feature was associated with significantly longer response times (RT) to the irrelevant probes (from 15.2 seconds after one trial to 24 seconds after 49 trials).…”
mentioning
confidence: 68%
See 3 more Smart Citations